2022
DOI: 10.1002/cbdv.202200143
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic, Antioxidant, and Antibacterial Properties of Vitex Agnus‐Castus L. Seed Extract: Assessment of Its Phenolic Content by LC/MS/MS

Abstract: In this current study, Vitex agnus-castus seed ethanol extracts were analyzed for their phytochemical component content, anticholinergic and antioxidant activities, and antibacterial properties. The phenolic compound composition of these seeds was determined by using LC/MS/MS. Antioxidant activity of the seeds was examined by the DPPH, ABTS, Fe 3 + -Fe 2 + reducing, and CUPRAC. Also, the anticholinergic activity was measured by the inhibition of acetylcholinesterase (AChE). The antibacterial activity was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…It was stated that samples with high total phenolic and flavonoid content showed high activity (Stavropoulou et al, 2021). There are numerous other studies in the literature that provide supportive evidence for this claim (Al-Khayri et al, 2022;Kavaz et al, 2022;Kavaz Yüksel et al, 2021;Tohma et al, 2015). According to the results obtained from our study, higher radical scavenging activity was found at the concentration of 30 μg mL −1 compared to other literature studies mentioned above.…”
Section: Devequisupporting
confidence: 82%
“…It was stated that samples with high total phenolic and flavonoid content showed high activity (Stavropoulou et al, 2021). There are numerous other studies in the literature that provide supportive evidence for this claim (Al-Khayri et al, 2022;Kavaz et al, 2022;Kavaz Yüksel et al, 2021;Tohma et al, 2015). According to the results obtained from our study, higher radical scavenging activity was found at the concentration of 30 μg mL −1 compared to other literature studies mentioned above.…”
Section: Devequisupporting
confidence: 82%
“…The absorbances of the mixtures were read at 700 nm to determine the iron-reducing capacity. Results were compared with standard reference compounds [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plants, which possess medicinal properties, can be employed as therapeutic or preventive solutions for various health issues (Kavaz et al, 2022). The lemon (Citrus × limon (L) Burm.…”
Section: )mentioning
confidence: 99%